Mendelian randomization to evaluate the causal relationship between liver enzymes and the risk of six specific bone and joint-related diseases - Huang, Guiwu; Li, Wenchang; Zhong, Yonglie; Liao, Weiming; Zhang, Zhiqi (Frontiers in Immunology, 2023)
Background: Studies of liver disfunction in relation to bone and joint-related diseases are scarce and its causality remains unclear. Our objective was to investigate whether serum liver enzymes are causally associated with bone and joint-related diseases using Mendelian randomization (MR) designs. Methods: Genetic data of serum liver enzymes (alkaline phosphatase, ALP; alanine transaminase, ALT; gamma-glutamyl transferase, GGT) and six common bone and joint-related diseases (rheumatoid arthritis (RA), osteoporosis, osteoarthritis (OA), ankylosing spondylitis, psoriatic arthritis, and gout) were derived from independent genome-wide association studies of European ancestry. The inverse variance-weighted (IVW) method was applied for the main causal estimate. Complementary sensitivity analyses and reverse causal analysis were utilized to confirm the robustness of the results. Results: Using the IVW method, the positive causality between ALP and risk of osteoporosis diagnosed by bone mineral density (BMD) at different sites was indicated (femoral neck, lumbar spine and total body BMD, odds ratio (OR) [95% CI], 0.40 [0.23–0.69], 0.35 [0.19–0.67] and 0.33 [0.22–0.51], respectively). ALP was also linked to higher risk of RA (OR [95%CI], 6.26 [1.69–23.51]). Evidence of potential harmful effects of higher level of ALT on risk of hip and knee OA were acquired (OR [95% CI], 2.48 [1.39–4.41] and 3.07 [1.49–6.30], respectively). No causal relationship was observed between GGT and these bone and joint-related diseases. The study also found that BMD were all negatively linked to ALP levels (OR [95%CI] for TBMD, FN-BMD, LS-BMD, 0.993 [0.991-0.995], 0.993 [0.988-0.998] and 0.993 [0.989,0.998] respectively) in the reverse causal analysis. The results were replicated via sensitivity analysis in the validation process. Conclusions: Our study revealed a significant association between liver function and bone and joint-related diseases. Keywords: Mendelian randomization, Liver enzyme, Bone and joint-related diseases, Causality, Genome-wide association studies